A Unique Pleomorphic Adenoma in the Minor Salivary Glands of the Upper Lip: A Case Report - Alrehaili J (Dove Medical Press, 2023)
Jihad Alrehaili Department of Pathology, College of Medicine, Imam Mohammad Ibn Saud Islamic University (IMSIU), Riyadh, Saudi ArabiaCorrespondence: Jihad Alrehaili, Tel +966-112037100, Email jaalrehaili@imamu.edu.saAbstract: Pleomorphic adenoma (PA) is a common benign tumor of the salivary glands, but its occurrence in the minor salivary glands of the upper lip is rare. In the a case report of a 24-year-old female with PA of the minor salivary glands in the upper lip, exhibiting unique histological characteristics such as features resembling schwannoma, keratinization, myxolipomatous, oncocytic, and mucinous traits resembling mucoepidermoid carcinoma. The main symptom of this condition is a gradual painless enlargement of the affected area. Histopathological analysis confirmed the diagnosis of PA. This case highlights the importance of public education in recognizing and treating painless masses. Further research is needed to explore PA's histological and molecular characteristics to establish prognostic factors such as the risk of recurrence.Keywords: pleomorphic adenoma, salivary glands, upper lip, painless mass